Karakteristik ibu hamil dengan hiperemesis gravidarum di RSUP Sanglah Denpasar tahun 2017 - Luh Putu Mahatya Valdini Putri; A. A. Gede Putra Wiradnyana; I Made Darmayasa (DiscoverSys Inc., 2019)
Background: Hyperemesis gravidarum is severe and over vomiting suffered as of early in pregnancy until 20 weeks of gestation. It may be harmful to the mother's health that can lead to weight loss of more than 5% and cause metabolic disorders. If it does not get proper treatment, it affects complications, even maternal and fetal deaths.Aim: The study aims to generalize the characteristic of pregnant patients who suffered hyperemesis gravidarum in Sanglah General Hospital.Method: This study is a cross sectional retrospective descriptive study with data retrieval on patient records for one year in 2017. This research was conducted at Space Cempaka Obstetrics and Medical Record Division Sanglah Hospital Denpasar.Result and Conclusion: pregnant women with hyperemesis gravidarum based on motherâ€™s age is highest experienced by pregnant women in the age group 20-35 years as many as 6 people (75%). Based on maternal age, pregnant women with hyperemesis gravidarum is highest experienced by pregnant women in the first trimester as many as 5 people (62.5%). As regard with the parity, Â it was highest experienced by pregnant women in the parity group nullipara as many as 4 people (50%). Moreover, maternal education is highest academic of pregnant women who have junior high and high school education, each of them as many as 3 people (37.5%). Based on the job status is highest experienced by pregnant women who work as many as 5 people (62.5%).